2010
DOI: 10.1063/1.3330678
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal gold nanosphere dispersions in smectic liquid crystals and thin nanoparticle-decorated smectic films

Abstract: We demonstrate that the layer structure and elasticity stabilize dispersions of colloidal nanoparticles in smectic liquid crystals. We use surface plasmon resonance spectra of gold nanospheres to probe their spatial distributions in the bulk of smectic lamellae. The average interparticle distances between the well-separated nanoinclusions in thin ͑Ͻ100 nm͒ smectic films are probed by atomic force microscopy. We show that limited motion of nanoparticles across layers due to the one-dimensional quasi-long-range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…This is associated with developing theoretical studies, including such basic approaches for the physics of liquid crystals as the Maier-Saupe or Landau-de-Gennes models [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, there are neither theoretical predictions nor experimental results regarding the form of pretransitional effects.…”
Section: Basics For the Isotropic -Mesophase Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is associated with developing theoretical studies, including such basic approaches for the physics of liquid crystals as the Maier-Saupe or Landau-de-Gennes models [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, there are neither theoretical predictions nor experimental results regarding the form of pretransitional effects.…”
Section: Basics For the Isotropic -Mesophase Transitionmentioning
confidence: 99%
“…It is indicated that the electric field associated with NPs can influence the local orientational ordering, increase the isotropicnematic (I-N) transition temperature or decrease the switching voltage [1,2,[10][11][12]. All these have led to an increase of theoretical and experimental interest in LC-based nanocolloids [17][18][19][20][21][22][23][24][25][26][27][28][29]. Regarding experiments, particularly important are dielectric studies since they are strongly associated with practical implementations and their results can be compared with fundamental models of the physics of liquid crystal .…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by using one of two general approaches; either by simple mixing of the two species [ 126 ], or modifying the surface chemistry of the particles and functionalizing them with liquid crystalline ligands [ 15 ]. Whilst these self-assembly techniques work to a large extent they suffer from the relatively low solubilities of the NPs in the host and the maximum size of the particles that it is possible to incorporate, although it has been reported that particles of up to 7 nm in diameter have been included in such systems [ 15 ].…”
Section: Referential Fabrication Techniquesmentioning
confidence: 99%
“…In the works [4,5], being based on studies of the optical characteristics inherent to the mixture of ANP with LC, it was shown that aggregation of ANP can be reduced if using LC that has a smectic phase. The change in the optical or electrooptical properties of ferroelectric LC, when introducing ANP, was considered in [6][7][8][9]. The influence of ANP on non-linear optical properties of LC was studied in [10].…”
Section: Introductionmentioning
confidence: 99%